Tinjauan tentang splin oklusal untuk terapi gangguan sendi temporomandibula A review about occlusal splint as a therapy for temporomandibular disorders - Ricca Chairunnisa; Erna Kurnikasari (DiscoverSys Inc., 2013)
An occlusal splint is a removable appliance usually made of acrylic, that fits over the occlusal and incisal surfaces ofthe teeth in one arch, creating precise occlusal contact with the teeth of the opposing arch. Occlusal splint has severalfunctions, one of which is to temporarily provide an temporary occlusion that allows the temporomandibular joints(TMJ) to make the most othopedically stable joint position. Occlusal splint is also used to protect the teeth and itssupportive structure from abnormal forces that may create breakdown and/or tooth wear. Occlusal splint is reversibleand noninvasive treatment, which is most important in treating temporomandibular disorders (TMD) with manycausative factors involved. Many types of splints have been suggested for the treatment of TMD, but the most frequentlyused are the stabilization splint and the anterior positioning splint. The purpose of this paper is to describe the types ofocclusal splints and indication used for the treatment of TMD.